A knowledge management perspective of supplier development: Evidence from supply chain scholars and consultants. (8th May 2018) - Chen, Liang; Ellis, Scott; Holsapple, Clyde
Abstract : As a critical supply chain management strategy and topic, supplier development has been intensively used in industries and actively studied in academia. A recent comprehensive review indicates an increasing interest in incorporating knowledge management in supply chain management, but supplier development has been rarely researched from the perspective of knowledge management. This study incorporates the knowledge chain theory to supplier development and investigates the importance of each knowledge management activity in supplier development. Using the survey data from a sample of active scholars and consultants who are committed to supplier development, this study supports the significant role of knowledge management in supplier development. Specifically, these scholars and consultants suggest that both buying and supplying firms should at least moderately conduct each knowledge management activity in supplier development in order to achieve desired outcomes. We also find that the roles of buying and supplying firms vary across 9 knowledge management activities. In addition, our respondents indicate that the definition of supplier development raised based on the the knowledge chain theory is at least moderately successful in all the evaluation criteria. Based on the quantitative and qualitative evidence from our respondents, this study revises the definition slightly to make it more comprehensive and clear. This study contributes to extant research by confirming the necessity of implementing knowledge management activities in supplier development, validating the heterogeneous roles of knowledge management activities in supplier development, and raising a revised definition of supplier development from the knowledge management perspective.